2015
DOI: 10.1093/schbul/sbv091
|View full text |Cite|
|
Sign up to set email alerts
|

Specificity of Incident Diagnostic Outcomes in Patients at Clinical High Risk for Psychosis

Abstract: It is not well established whether the incident outcomes of the clinical high-risk (CHR) syndrome for psychosis are diagnostically specific for psychosis or whether CHR patients also are at elevated risk for a variety of nonpsychotic disorders. We collected 2 samples (NAPLS-1, PREDICT) that contained CHR patients and a control group who responded to CHR recruitment efforts but did not meet CHR criteria on interview (help-seeking comparison patients [HSC]). Incident diagnostic outcomes were defined as the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 75 publications
7
67
1
Order By: Relevance
“…33 Recent original studies in UHR individuals ( n = 271) as contrasted to comparison individuals ( n = 171) further confirmed no evidence of diagnostic pluripotentiality with respect to new or incident anxiety, bipolar, or non-bipolar mood disorders. 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 Recent original studies in UHR individuals ( n = 271) as contrasted to comparison individuals ( n = 171) further confirmed no evidence of diagnostic pluripotentiality with respect to new or incident anxiety, bipolar, or non-bipolar mood disorders. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that CHR-P individuals are not at risk for developing incident bipolar disorders, nonbipolar mood disorders or anxiety disorders 15 compared to control groups and that the vast majority of comorbid disorders observed in CHR-P individuals who do not develop psychosis is already present at the baseline. 16 These findings advance knowledge indicating that the possible outcomes specifically associated with the CHR-P (which may be preferred to the acronym "CHR" to better acknowledge the specificity for psychosis prediction) designation may include the onset of psychotic disorders, remission or persistence of initial symptoms and variable functional outcomes 17 but not an increased risk of emergence of new (incident) nonpsychotic mental disorders.…”
Section: Specificity For Psychosis Predictionmentioning
confidence: 93%
“…Their risk peaks in the first two years 59 and is specific for the development of psychotic disorders but not for emerging non-psychotic disorders 60,61 . However, less than half of those who will not develop psychosis will eventually remit (35% of the baseline cohort) 62 , since persistent comorbidities (that were already present at baseline [63][64][65] ) and functional impairment are frequently observed at follow-up 64 .…”
Section: State Of the Artmentioning
confidence: 99%